PENERAPAN AJUDIKASI KHUSUS OLEH OMBUDSMAN REPUBLIK INDONESIA TERHADAP PENYELENGGARA NEGARA YANG MALADMINISTRASI - Andi Anas Chaerul M. (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2020)
Abstract               The Ombudsman carries out the function of settling public service disputes in terms of settling compensation, one of which is through special adjudication as stipulated in RI Law Number 25 of 2009 concerning Public Services. However, the fact is that until now the Special Adjudication mechanism has never been implemented. The application of Special Adjudication by the Ombudsman of the Republic of Indonesia to state administrators who were maladministrated was ineffective. Factors affecting the ineffectiveness of the application of the Special Adjudication by the Ombudsman to state administrators who are maladministrated are legal factors in the absence of implementing regulations (Presidential Regulation) governing the mechanisms and provisions for compensation payments, factors for charging compensation, and human resource factors and facilities infrastructureKeywords: Ombudsman, Special Adjudication                        AbstrakOmbudsman melaksanakan fungsi penyelesaian sengketa pelayanan publik dalam hal penyelesaian ganti rugi yang salah satunya melalui jalan ajudikasi khusus sebagaimana diatur dalam Undang-Undang RI Nomor 25 Tahun 2009 Tentang Pelayanan Publik. Namun, faktanya hingga saat ini mekanisme Ajudikasi Khusus belum pernah dilaksanakan. Penerapan Ajudikasi Khusus oleh Ombudsman Republik Indonesia terhadap penyelenggara negara yang maladministrasi tidak efektif. Faktor-faktor yang mempengaruhi tidak efektifnya penerapan Ajudikasi Khusus oleh Ombudsman terhadap penyelenggara negara yang maladministrasi adalah faktor hukum dengan tidak adanya aturan pelaksana (Peraturan Presiden) yang mengatur mekanisme dan ketentuan pembayaran ganti rugi, faktor pembebanan ganti kerugian, dan faktor sumber daya manusia dan sarana prasaranaKata Kunci :  Ombudsman, Ajudikasi Khusus